Perancangan Sistem Informasi Pendaftaran Rawat Jalan Pasien RSU PKU Muhammadiyah Bantul Yogyakarta Berbasis Web - Pradiatiningtyas, Diah; - UBSI Yogyakarta, Kusnadi (Indonesian Journal of Networking and Security (IJNS), 2019)
Abstract - PKU Muhammadiyah Hospital Bantul is one hospital that has implemented a computerized information system in the patient service process. However, there are obstacles in its application, including complaints from patients with length of queue. This phenomenon results in delays in handling patients who have arrived at the hospital. The purpose of this final project is to design a website-based online outpatient registration program. By designing a new computerized information system to improve the efficiency and effectiveness of both officers and patients. Data collection techniques are carried out by means of interviews, observation and literature study. Waterfall methods was use and blackbox testing. With the help of web utilization, it can be more helpful for companies in delivering information on superior services and products they have. Because making registration online so that patients who have registered can be easy by knowing the serial number of turn and can estimate the time of arrival at the hospital. In general, the results of the application made is an online registration application that assists in the delivery of information on medical services in hospitals and online registration. Key Words: Design, System, Registration, Outpatient, Hospital Abstrak - RSU PKU Muhammadiyah Bantul adalah salah satu rumah sakit yang sudah menerapkan sistem informasi komputerisasi di dalam proses pelayanan pasien. Namun terdapat kendala di dalam penerapannya, diantaranya seperti komplain dari pasien dengan lamanya antrian. Fenomena ini mengakibatkan tertundanya penanganan pasien yang sudah tiba di rumah sakit. Tujuan dari penulisan tugas akhir ini adalah membuat rancangan program pendaftaran pasien rawat jalan online berbasis website. Dengan membuat rancangan sistem informasi komputerisasi yang baru agar meningkatkan efisiensi dan efektifitas petugas maupun pasien. Teknik pengumpulan data dilakukan dengan cara wawancara, observasi dan studi pustaka serta menggunakan metode waterfall untuk perancangannya dan pengujian blackbox. Dengan bantuan pemanfaatan web bisa lebih membantu perusahaan dalam penyampaian informasi jasa dan produk unggulan yang dimilikinya. Sebab membuat pendaftaran secara online agar pasien yang telah terdaftar dapat kemudahan dengan mengatahui nomor urut giliran dan dapat memperkirakan waktu tiba di rumah sakit. Secara umum hasil aplikasi yang dibuat adalah aplikasi pendaftaran online yang membantu dalam penyampaian informasi layanan jasa pengobatan di rumah sakit dan pendaftaran online. Kata Kunci: Perancangan, Sistem, Pendaftaran, Rawat Jalan, Rumah Sakit.